A Near‐Infrared Organic Fluorescent Probe for Broad Applications for Blood Vessels Imaging by High‐Throughput Screening via 3D‐Blood Vessel Models. Issue 8 (16th June 2021) - Abdul Sisak, Muhammad Asri; Louis, Fiona; Aoki, Ichio; Lee, Sun Hyeok; Chang, Young‐Tae; Matsusaki, Michiya
Abstract: Blood vessels are present in all of the organs, reflecting their importance for oxygen and nutrient delivery to the cells. Until now, no organic fluorophore has been reported for the live imaging of endothelium although the layer is the key to blood vessel functions. Here, the discovery of a blood vessel organic probe at near‐infrared (NIR) wavelength range (BV‐NIR) through an engineered blood capillary‐based screening system, which is a more physiological model than a conventional cell culture condition, is reported. This selected Cy5 based probe shows the highest specific adsorption property out of 240 candidates on the endothelium and is equivalent to an anti‐CD31 antibody in terms of intensity. The BV‐NIR probe indicating strong and stable in vitro, ex vivo, and in vivo imaging of the endothelium even after histological immunostaining processes shows potential as a convenient tool for live imaging as well as for covisualization with a specific antibody. Abstract : Unbiased screening of diversity‐oriented fluorescence library is promising. This study reports the discovery of an NIR blood vessel organic probe through an engineered 3D blood capillary‐based screening system. This reliable screening system is more physiological with higher cell surface marker expression in endothelial cells than a conventional cell culture screening in 2D.